2009
DOI: 10.1108/17465660911006431
|View full text |Cite
|
Sign up to set email alerts
|

Modelling traditional accounting and modern value‐based performance measures to explain stock market returns in the Athens Stock Exchange (ASE)

Abstract: Purpose -The purpose of this paper is to investigate the explanatory power of two value-based performance measurement models, Economic Value Added (EVA w ) and shareholder value added (SVA), compared with three traditional accounting performance measures: earnings per share (EPS), return on investment (ROI), and return on equity (ROE), in explaining stock market returns in the Athens Stock Exchange (ASE). Design/methodology/approach -The paper uses the Easton and Harris formal valuation model and employs both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
7
21
0
3
Order By: Relevance
“…Studies which found economic-based measures to be more useful rather than accounting-based variables included studies by Stewart (1991Stewart ( , 1994, Stern (1993), Milunovich and Tsuei (1996), O'Byrne (1996), Bacidore et al (1997), Dodd (1997, 2001), Hall (1999), Worthington and West (2004), Chmelikova (2008) and Lee and Kim (2009). By contrast, studies by Biddle et al (1997), Salvaiy (1997), Bao and Bao (1998), De Villiers and Auret (1998), De Wet (2005, Ismail (2006), Maditinos et al (2006Maditinos et al ( , 2009, Kyriazis and Anastassis (2007), Erasmus (2008), Kumar and Sharma (2011), Arabsalehi and Mahmoodi (2012), Abdoli et al (2012), Mollah et al (2012), Hall (2013) and Alloy Niresh and Alfred (2014) found that accounting-based variables performed better in explaining shareholder value creation than economic-based measures. It falls beyond the scope of this study to discuss the results of the abovementioned studies in more detail, but it is important to point out that the inconsistencies of their results may lead managers, investors, shareholders and researchers to ask the following questions:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies which found economic-based measures to be more useful rather than accounting-based variables included studies by Stewart (1991Stewart ( , 1994, Stern (1993), Milunovich and Tsuei (1996), O'Byrne (1996), Bacidore et al (1997), Dodd (1997, 2001), Hall (1999), Worthington and West (2004), Chmelikova (2008) and Lee and Kim (2009). By contrast, studies by Biddle et al (1997), Salvaiy (1997), Bao and Bao (1998), De Villiers and Auret (1998), De Wet (2005, Ismail (2006), Maditinos et al (2006Maditinos et al ( , 2009, Kyriazis and Anastassis (2007), Erasmus (2008), Kumar and Sharma (2011), Arabsalehi and Mahmoodi (2012), Abdoli et al (2012), Mollah et al (2012), Hall (2013) and Alloy Niresh and Alfred (2014) found that accounting-based variables performed better in explaining shareholder value creation than economic-based measures. It falls beyond the scope of this study to discuss the results of the abovementioned studies in more detail, but it is important to point out that the inconsistencies of their results may lead managers, investors, shareholders and researchers to ask the following questions:…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are numerous studies that have argued that EVA is not superior to other measures and even it is not a significant performance measure to be considered in decision making. Dodd (1997, 1998); Biddle, Bowen and Wallace (1997); Worthington and West (2001); Kim (2006);Ismail (2006) and Maditinos, Sevic and Theriou (2009) have reported that though EVA shows a relationship with return, the EVA is not a superior performance measure as argued by Stewart (1991) . Some other researchers (Peterson and Peterson, (1996) ;Turvey et.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We use a model developed by Easton & Harris (1991) and has been used by many researchers such as Easton & Harris (1991), Biddle, et al (1997), Chen & Dodd (1997) and Worthington & West (2001). Easton & Harris (1991) model is a connection between stock returns, earnings levels and changes in the level of each earnings as quotes in study by Maditinos et al (2009). Based on the explanation above, the model is developed from Easton and Harris's Model to analyze the relationship between Economic Value Added (EVA) and the company's financial ratios with company's stock return based on study done by Maditinos et al (2009) and this model is also used on study by Mandilas et al (2009).…”
Section: = ℎmentioning
confidence: 99%
“…Above study is a continuation of research conducted by Maditinos, Sevic, & Theriou (2009) with the same sample but different research study period with the method developed by Easton & Harris (1991) namely relative information content and incremental information content. This study also found the same thing with the above studies is that the EPS has the greatest explanatory power on the stock return and if EVA combined with the EPS, the explanatory power of these measurements both in the stock return is greater than the explanatory power of each variable (i.e.…”
Section: Introductionmentioning
confidence: 99%